Co-design of an oral health intervention (HABIT) delivered by health visitors for parents of children aged 9-12 months - Jenny Owen; Kara A. Gray-Burrows; Ieva Eskytė; Faye Wray; Amrit Bhatti; Timothy Zoltie; Annalea Staples; Erin Giles; Edwina Lintin; Robert West; Sue Pavitt; Rosemary R. C. McEachan; et al. (BMC, 2022)
Abstract Background Dental caries (tooth decay) in children is a national public health problem with impacts on the child, their family and wider society. Toothbrushing should commence from the eruption of the first primary tooth. Health visitors are a key provider of advice for parents in infancy and are ideally placed to support families to adopt optimal oral health habits. HABIT is a co-designed complex behaviour change intervention to support health visitors' oral health conversations with parents during the 9-12-month universal developmental home visit. Methods A seven stage co-design process was undertaken: (1) Preparatory meetings with healthcare professionals and collation of examples of good practice, (2) Co-design workshops with parents and health visitors, (3) Resource development and expert/peer review, (4) Development of an intervention protocol for health visitors, (5) Early-phase testing of the resources to explore acceptability, feasibility, impact and mechanism of action, (6) Engagement with wider stakeholders and refinement of the HABIT intervention for wider use, (7) Verification, Review and Reflection of Resources. Results Following preparatory meetings with stakeholders, interviews and co-design workshops with parents and health visitors, topic areas and messages were developed covering six key themes. The topic areas provided a structure for the oral health conversation and supportive resources in paper-based and digital formats. A five-step protocol was developed with health visitors to guide the oral health conversation during the 9-12 month visit. Following training of health visitors, an early-phase feasibility study was undertaken with preliminary results presented at a dissemination event where feedback for further refinement of the resources and training was gathered. The findings, feedback and verification have led to further refinements to optimise quality, accessibility, fidelity and behaviour change theory. Conclusion The co-design methods ensured the oral health conversation and supporting resources used during the 9-12 month visit incorporated the opinions of families and Health Visitors as well as other key stakeholders throughout the development process. This paper provides key learning and a framework that can be applied to other healthcare settings. The structured pragmatic approach ensured that the intervention was evidence-based, acceptable and feasible for the required context. Trial registration ISRCTN55332414, Registration Date 11/11/2021.